Literary reading in child education: what spaces and times are these? - Thamirys Frigo Furtado; Eliane Santana Dias Debus (Universidade Federal de Santa Catarina, 2017)
http://dx.doi.org/10.5007/1980-4512.2017v19n35p133 When thinking about the formation of children-readers, it is essential to reflect on time and space available for the pedagogical actions that involve reading and literature. Thus, this article presents partial discussions carried out in a master's degree research developed under the Post-Graduation Program in Education of the Federal University of Santa Catarina (UFSC), with the objective of map the collective time and space of literary reading in the Child Education Institutions of the Florianópolis Municipal School System (SC). Data analysis has led us to see that most of the units have different collective space and time of literary reading, organized and planned by the teachers and other staff of the institution, considering that there is no library in every institution. With this, we conclude that there are professionals concerned with bringing children closer to literate culture, actively participating in the training of small readers, inventing and reinventing new possibilities every day.